Innovation of Business Curriculum in Elementary Schools: Implementation of Market Day and Business Day Activities - Syifa Sholihatul Qowi'ah; Imam Makruf (Universitas KH. Mukhtar Syafaat Blokagung Banyuwangi, 2025)
This study aims to explain how to implement Market Activity Day and Business Day in the business curriculum at SD Alam Aqila Klaten Central Java. The method used is a qualitative approach with a case study method. Data collection techniques through interviews, direct observation, and documentation. Data analysis is by data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of market day and business day activities in the business curriculum uses 3 stages, namely 1) The planning stage of market day activities in the form of holding work meetings to determine the implementation time, learning targets/achievements, regulations and themes at each level. 2 ) The implementation stage includes production, distribution and consumption process activities. The production process is carried out by students who can be assisted by parents at home, carried out in groups at school from the process of creating ideas, production to the end of making reports. The distribution process is carried out by individual students by instilling the principles of honesty, orderliness and responsibility, the teacher only observes and accompanies students during the activity. The consumption process is carried out by students, teachers and buyers by implementing eating and drinking etiquette and providing good experiences and habits , 3) The evaluation stage is carried out by the teacher providing reflection to students, observing the extent of students' success in achieving learning targets carried out in market day and business day activities and providing assessments using student portfolios.